Advanced spectroscopic analysis and 15N-isotopic labelling study of nitrate and nitrite reduction to ammonia and nitrous oxide by E. coli. Issue 22 (25th October 2021) - Metcalfe, George D.; Smith, Thomas W.; Hippler, Michael
Abstract : Nitrate and nitrite reduction to ammonia and nitrous oxide by E. coli is investigated by advanced spectroscopic analytical techniques and 15 N-isotopic labelling, with the simultaneous online measurement of up to 20 different species and parameters. Abstract : Nitrate and nitrite reduction to ammonia and nitrous oxide by anaerobic E. coli batch cultures is investigated by advanced spectroscopic analytical techniques with 15 N-isotopic labelling. Non-invasive, in situ analysis of the headspace is achieved using White cell FTIR and cavity-enhanced Raman (CERS) spectroscopies alongside liquid-phase Raman spectroscopy. For gas-phase analysis, White cell FTIR measures CO2, ethanol and N2 O while CERS allows H2, N2 and O2 monitoring. The 6 m pathlength White cell affords trace gas detection of N2 O with a noise equivalent detection limit of 60 nbar or 60 ppbv in 1 atm. Quantitative analysis is discussed for all four 14 N/ 15 N-isotopomers of N2 O. Monobasic and dibasic phosphates, acetate, formate, glucose and NO3 − concentrations are obtained by liquid-phase Raman spectroscopy, with a noise equivalent detection limit of 0.6 mM for NO3 − at 300 s integration time. Concentrations of the phosphate anions are used to calculate the pH in situ using a modified Henderson–Hasselbalch equation. NO2 − concentrations are determined by sampling for colorimetric analysis and NH4 + by basifying samples to release 14 N/ 15 N-isotopomers of NH3 for measurement in a second FTIR White cell. The reductions of 15 NO3 −, 15 NO2 −, and mixed 15 NO3 − and 14 NO2 − by anaerobic E. coli batch cultures are discussed. In a major pathway, NO3 − is reduced to NH4 + via NO2 −, with the bulk of NO2 − reduction occurring after NO3 − depletion. Using isotopically labelled 15 NO3 −, 15 NH4 + production is distinguished from background 14 NH4 + in the growth medium. In a minor pathway, NO2 − is reduced to N2 O via the toxic radical NO. With excellent detection sensitivities, N2 O serves as a monitor for trace NO2 − reduction, even when cells are predominantly reducing NO3 − . The analysis of N2 O isotopomers reveals that for cultures supplemented with mixed 15 NO3 − and 14 NO2 − enzymatic activity to reduce 14 NO2 − occurs immediately, even before 15 NO3 − reduction begins. Optical density and pH measurements are discussed in the context of acetate, formate and CO2 production. H2 production is repressed by NO3 − ; but in experiments with NO2 − supplementation only, CERS detects H2 produced by formate disproportionation after NO2 − depletion.